Who decides in withdrawal of treatment in a critical care setting? A case study on ethical dilemma - Chunmei Lyu; Li Zhang (Elsevier, 2018)
Case description: Withdrawal of treatment is a common practice in critical care settings, perticularly when treatment is considered futile. The case study demonstrates an ethical dilemma, in which Danny is unlikely to make a functional recovery because of multiple organ dysfunction syndromes. Under such a circumstance, withdrawal of treatment will inevitably be considered, although his family refused to do so. Consequently, acritical question must be answered: Who should make the decision? Ethical dilemma identification: Danny decided to withdraw the use of life-support, whilst his wife and adult children refused to do so. The ethical dilemma is illustrated by the following question: Who decides the withdrawal of treatment in a critical care setting? Analysis: To provide an opotional solution to this case and make the best moral decision, the current study will critically discuss this issue in conjunction with ethical principles, philosophical theories and the values statement of the European and Chinese nurses' codes of ethics. Additionally, the associated literature relative to this case are analysed before the decision-making. Ethical decision-making: The best ethical decision is Danny can decide whether to withhold or withdraw life-sustaining treatment. If his family is involved in the discussion, the medical staff should balance the ethical principles when they make the decision and allocate reasonable resources for patients. Results: In Danny's case, health professionals opted to respect his decision to withdraw treatment. The medical staff maintained an effective communication with the family involved, and provided the appropriate intervention to collaborate with other health care professionals to perfect further care. Keywords: Codes of ethics, Critical care, Decision-making, Ethical dilemmas, Medical futility, Morals